2017
DOI: 10.1016/j.bbadis.2017.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell calpain as a critical modulator of angiogenesis

Abstract: Calpains are a family of calcium-dependent non-lysosomal cysteine proteases. In particular, calpains residing in the endothelial cells play important roles in angiogenesis. It has been shown that calpain activity can be increased in endothelial cells by growth factors, primarily vascular endothelial growth factor (VEGF). VEGF/VEGFR2 induces calpain 2 dependent activation of PI3K/AMPK/Akt/eNOS pathway, and consequent nitric oxide production and physiological angiogenesis. Under pathological conditions such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 127 publications
(185 reference statements)
3
26
0
Order By: Relevance
“…However, it is noteworthy that Capn1 -deficient mice as well as EC-specific Capn2 -deficient mice did not exhibit the lethal vascular defects 23 , 26 ) ; thus, the impact of calpain-dependent angiogenesis on physiological vascular regulations is currently unclear. Please refer to an excellent review for further details of calpain-mediated physiological angiogenesis 86 ) .…”
Section: Contribution Of Calpain Proteolytic Systems To Degenerative mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is noteworthy that Capn1 -deficient mice as well as EC-specific Capn2 -deficient mice did not exhibit the lethal vascular defects 23 , 26 ) ; thus, the impact of calpain-dependent angiogenesis on physiological vascular regulations is currently unclear. Please refer to an excellent review for further details of calpain-mediated physiological angiogenesis 86 ) .…”
Section: Contribution Of Calpain Proteolytic Systems To Degenerative mentioning
confidence: 99%
“…In this regard, growing evidence suggests that the calpain proteolytic systems, comprised of Ca 2+ -dependent intracellular proteases and a calpain endogenous inhibitor, critically contribute to degenerative vascular disorders. Calpains can be potentiated in the presence of pathophysiological stressors, such as inflammatory cytokines, growth factors, bioactive lipids and hypoxic stimulus 10 , 11 ) . As a result, dysregulation of these systems might be responsible for the vascular disorders noted above.…”
Section: Introductionmentioning
confidence: 99%
“…Calpains are calcium-dependent intracellular proteases that are activated by exogenous stressors such as physical stress, as well as by cytokines, growth factors, and hypoxia (11)(12)(13). In vascular endothelial cells (ECs), calpain systems are associated with sprouting angiogenesis (14,15). Our previous study showed that calpain proteolyzes suppressor of cytokine signaling 3 (an endogenous inhibitor of Janus kinase/signal transducers and activator of transcription signaling) in angiogenic ECs, sensitizing them to cytokine stimuli (16).…”
mentioning
confidence: 99%
“…CAPN3 is involved in multiple important functions (Zhang et al, 2017) and has drawn great research interest because of its three specific regions (N-terminal, IS1 and IS2) (Ono et al, 2016). For example, defects IS1/2 in CAPN3 lead to limb girdle muscular dystrophy type 2A (LGMD2A) symptoms and other disease (Beckmann and Spencer, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Calpains are Ca 2+ -dependent intracellular cysteine proteases that are involved in cell motility (Glading et al, 2002), and apoptosis regulation (Liu et al, 2004), muscle atrophy (Richard et al, 1995), myoblast fusion (Honda et al, 2008), and muscle growth and develop-ment (Sultan et al, 2000;Zhang et al, 2009). To date, 15 isoforms have been identified in humans (Sorimachi and Ono, 2012), and in vertebrates, calpain 1 and calpain 2 have been widely studied among calpain isoforms (Macqueen et al, 2010;Zhang et al, 2017). Among the calpain family members, calpain 3 (CAPN3, previously named p94) is particularly interesting, because in humans, limb-girdle muscular dystrophy type 2A (LGMDA2) is mainly caused by lossof-function mutations of CAPN3 (Richard et al, 1995).…”
Section: Introductionmentioning
confidence: 99%